Global transition to innovative economic pattern development and formation of postindustrial management - Prudskiy V. (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
Innovative components in the system of competitive management of economic patterns and forming of postindustrial management are analysed in the article.